Fetotoxicity and Subacute Toxicity of Some Plants Involved in the Treatment of Infectious Diarrhea in Benin - Hounsa, Edna; Dougnon, Tamegnon Victorien; Agbankpe, Alidehou Jerrold; Assogba, Phénix; Koudokpon, Charles Hornel; Klotoe, Jean-Robert; Moussa, Rachida Tari; Agbodjento, Eric; Fabiyi, Kafayath; Deguenon, Esther; Bankole, Honore Sourou; Diallo, Aboudoulatif (Frontiers in Tropical Diseases, 2022)
This study aimed to provide data on the subacute toxicity and fetotoxicity of aqueous and hydroethanolic extracts of Daniellia oliveri (Rolfe) Hutch. & Dalziel, Anacardium occidentale L., Diospyros mespiliformis Hochst. ex A. DC., Khaya senegalensis (Desv.) A. Juss., Ocimum gratissimum L., Vernonia amygdalina Delile, Pterocarpus erinaceus Poir., and Manihot esculenta Crantz used in the treatment of diarrheal diseases in Benin. For subacute toxicity, each male and female Wistar rat received by esophageal gavage a maximum of 1000 mg/kg over 28 days following the Organization for Economic Co-operation and Development (OECD) Guideline No. 407. Bodyweight changes, biochemical and hematological parameters were assessed. The fetotoxicity of the extracts was evaluated on Dutch Blue hen eggs at 100 mg/kg and 300 mg/kg. The hatching rate, biochemical and hematological constants were subsequently determined. The subacute toxicity data did not indicate any mortality or signs of toxicity. Also, no significant difference in the bodyweight of the rats and the hematological parameters was noted. Concerning fetotoxicity, a low hatching rate (varying from 20% to 50%) was observed in the batches treated with the extracts at 300mg/kg compared to the rate obtained in the negative control batch (80%). The batches that received the hydroethanolic extracts of Vernonia amygdalina and Manihot esculenta at the tested doses had a hatching rate of 0%. When looking at hematological parameters, no significant difference was noted for all batches. However, an increase in the Aspartate Amino-Transferase (ASAT) values was noted in the batches that received the hydroethanolic extract of Khaya senegalensis and the aqueous extract of Diospyros mespiliformis at 100 and 300 mg/kg. These results explicitly show that the hydroethanolic extracts of Manihot esculenta and Vernonia amygdalina are fetotoxic at the tested doses.